(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted with the aim of demonstrating the effect of adding black maca to improve semen quality at different concentrations by oral for Awassi rams. The study included tests of fresh semen. 12 rams of the Awassi breed were used, with three rams. adults aged 2.5-3.5 years for each group, The semen was collected using an artificial vagina for sheep and goats at the rate of one ejaculate/ram/week, for a period of 12 weeks. The semen of the rams (pooled semen) was mixed in order to eliminate individual differences between the rams. The sample was divided equally among the experimental groups using Tris diluent with a dilution ratio of 1:20, and the rams were dosed with different concentrations, which amounted to (10g, 20g, 40g Maca Black), which are represented by (T1, T2, T3) treatments, respectively, compared with the control group without the addition of black maca (0 g). The necessary tests were performed to evaluate the semen in terms of ejaculate volume, individual and mass activity, concentration, and testosterone. The results of the experiment showed that adding and dosing 20 grams of black maca powder to Awassi rams had a significant effect on some characteristics of fresh semen, as individual sperm motility increased, accompanied by a significant increase (p<0.05) of ejaculate volume, concentration, mass activity, testosterone in all the different treatments. Compared with the control group. It can be concluded that adding black maca at a concentration of (20 g) to the treatment (T2) led to improving the semen characteristics of Awassi rams.